An Open-Label Prospective Study to Compare the Efficacy and Safety of Topical Fluticasone Versus Tacrolimus in the Proactive Treatment of Atopic Dermatitis - Vinodhini R. Mudaliyar; Asha Pathak; Alok Dixit; Sweta Kumar (Mattioli1885, 2020)
Background: Atopic dermatitis (AD), a chronic recurrent inflammatory skin condition primarily affects children. Topical treatment, systemic treatment, and phototherapy are mainstay of treatment. Objectives: Topical corticosteroids (TCS) are the first line therapy for AD but are associated with various adverse effects. Topical calcineurin inhibitor (TCI) can be used as an alternative to TCS. The aim of the study is to compare efficacy of topical preparation of fluticasone and tacrolimus in lowering the severity of disease, to assess the quality of life (QoL), and to estimate if any association exists between them. Methods: 37 AD children, randomly received either of the two topical treatments, daily application for first 4 week of in acute phase and twice weekly for next 4 week as maintenance phase. The severity of disease was assessed using SCORing Atopic Dermatitis (SCORAD) and QoL was assessed by using Children's Dermatology Life Quality Index (CDLQI). Results:  At the end of acute phase, there was reduction in SCORAD score by 69.29% in fluticasone and 64.20% in tacrolimus group (P<0.001). In maintenance phase, the score had risen in fluticasone group by a mean difference of 0.81 while in tacrolimus, it decreased by 0.99. Both fluticasone and tacrolimus groups improved children's QoL (P<0.001). Positive correlation (r=0.4668) exists between the SCORAD and QoL. Skin burning was the most common ADR seen with tacrolimus. Conclusions: Fluticasone and tacrolimus are equally efficacious in the treatment of AD, with similar benefits on children's QoL. Tacrolimus is better in reducing the extent of lesions than fluticasone